Mitral valve prolapse syndrome - Sanecki, Miłosz; Jurasz, Karolina; Podgórska, Dominika; Tomczyk, Karolina; Chojnacka, Natalia; Rzeska, Ewa; Klarycki, Jakub; Cymer, Radosław (Journal of Education, Health and Sport, 2024)
Mitral valve prolapse is a common valvular defect. In its overt clinical form, the condition known as mitral valve leaflet prolapse syndrome, or also known as Barlow's syndrome or flaccid valve syndrome, is a significant clinical problem, worsening the quality of life of patients, and in its severe forms is a risk factor for diseases such as congestive heart failure, endocarditis or cardiac arrhythmias, or even lead to death from sudden cardiac death. The development of methods, as well as the increasing general availability of echocardiography methods, makes a specific diagnosis early enough to allow the right treatment strategy to be chosen. Thanks to reliable reports in recent years, it has been possible to identify a group of patients whose cardiovascular risk predisposes them to a more severe course of the disease and thus these patients require special observation and attention in the process of diagnosis and treatment. Recent years have allowed the development of a new method of interventional treatment in patients burdened with multimorbidity for whom conventional surgery would be associated with a significant risk of worsening of the general condition.